You're not welcome! Violence and support for an open grazing ban policy in Kaduna, Nigeria - Daniel Tuki (Environment and Security, 2024)
This study examines the effect of victimization and religious affiliation on support for a policy banning the open grazing of livestock in the northern Nigerian state of Kaduna. This policy, which aims to reduce the incidence of conflicts between nomadic herders and sedentary farmers, has been implemented to varying degrees in some states across Nigeria. Kaduna is a suitable case study for investigating these relationships because, despite having the third-highest incidence of farmer–herder conflicts out of Nigeria's 36 states, the state government has not implemented an open grazing ban policy there. The regression results show that victimization by herders increases the likelihood of supporting the policy. On average, Muslims are more supportive of the policy than Christians. The higher support among Muslims is quite surprising because most of the respondents who have been victimized by herders are Christians. Muslims might be more supportive of an open grazing ban policy due to a contagion effect: the common religion of Islam that they share with nomadic herders could lead to the attribution of blame for farmer–herder conflicts to Muslims, making them more eager to see an end to the conflict. This eagerness might be what leads to increased support for an open grazing ban policy.
https://doi.org/10.7910/DVN/JRMSFQ
Keywords: D74; N57; Z12; 330; religion; ethnicity; violence; open grazing ban; policy; farmer–herder conflicts; pastoral conflicts; Kaduna; Nigeria